Representaciones de género en iglesias bautistas de la ciudad de Matanzas, Cuba - Vichot Borrego, Laura (2024)
This article set out to analyze gender representations in members of the First Baptist Church and the Baptist Fraternity Church of the city of Matanzas. During the research process, from a qualitative perspective, observation, survey, content analysis of sermons, and semi-structured interviews with teologians and pastors were used as techniques. Despite being a religious médium sensitive to the perspective of inclusion and that denominationally responds to postulates of Liberation Theology, the predominant gender representations were attached to binary and cisheteropatriarchal.